Increased Voluntary Alcohol Consumption in Mice Lacking GABAB(1) Is Associated With Functional Changes in Hippocampal GABAA Receptors - Floris, Gabriele; Asuni, Gino Paolo; Talani, Giuseppe; Biggio, Francesca; Pisu, Maria Giuseppina; Zanda, Mary Tresa; Contu, Liliana; Maciocco, Elisabetta; Serra, Mariangela; Follesa, Paolo (Frontiers in Behavioral Neuroscience, 2022)
Gamma-aminobutyric acid type B receptor (GABABR) has been extensively involved in alcohol use disorders; however, the mechanisms by which this receptor modulates alcohol drinking behavior remain murky. In this study, we investigate alcohol consumption and preference in mice lacking functional GABABR using the 2-bottle choice paradigm. We found that GABAB(1), knockout (KO), and heterozygous (HZ) mice drank higher amounts of an alcoholic solution, preferred alcohol to water, and reached higher blood alcohol concentrations (BACs) compared to wild-type (WT) littermates. The GABABR agonist GHB significantly reduced alcohol consumption in the GABAB(1) HZ and WT but not in the KO mice. Next, because of a functional crosstalk between GABABR and δ-containing GABAA receptor (δ-GABAAR), we profiled δ subunit mRNA expression levels in brain regions in which the crosstalk was characterized. We found a loss of the alcohol-sensitive GABAAR δ subunit in the hippocampus of the GABAB(1) KO alcohol-naïve mice that was associated with increased ɣ2 subunit abundance. Electrophysiological recordings revealed that these molecular changes were associated with increased phasic inhibition, suggesting a potential gain of synaptic GABAAR responsiveness to alcohol that has been previously described in an animal model of excessive alcohol drinking. Interestingly, voluntary alcohol consumption did not revert the dramatic loss of hippocampal δ-GABAAR occurring in the GABAB(1) KO mice but rather exacerbated this condition. Finally, we profiled hippocampal neuroactive steroids levels following acute alcohols administration in the GABAB(1) KO and WT mice because of previous involvement of GABABR in the regulation of cerebral levels of these compounds. We found that systemic administration of alcohol (1.5 g/kg) did not produce alcohol-induced neurosteroid response in the GABAB(1) KO mice but elicited an expected increase in the hippocampal level of progesterone and 3α,5α-THP in the WT controls. In conclusion, we show that genetic ablation of the GABAB(1) subunit results in increased alcohol consumption and preference that were associated with functional changes in hippocampal GABAAR, suggesting a potential mechanism by which preference for alcohol consumption is maintained in the GABAB(1) KO mice. In addition, we documented that GABAB(1) deficiency results in lack of alcohol-induced neurosteroids, and we discussed the potential implications of this finding in the context of alcohol drinking and dependence.